A MODERN VIEW ON THE PHENOMENOLOGY OF SOCIAL-PSYCHOLOGICAL ADAPTATION AND MALADAPTATION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Changes are taking place at a rapid pace in modern society. Technological progress, social networks, globalization and economic changes have a great impact on the lives of young people. It is important to study how these changes affect the social adjustment of young people and how they adapt to new conditions.